Catasetum × ronaldoi: the first natural hybrid of the genus for the northeastern of Brazil and taxonomic notes for C. purum - Krahl, Dayse R. P.; Schmal, Philippe; Chiron, Guy; Silva, João B. F. Da; Krahl, Amauri H.; Cantuária, Patrick De C. (Phytotaxa, 2026)
This article reports the first record of a Catasetum nothospecies in the Brazilian Northeast, more precisely in the state of Bahia. The proposed new entity is described and illustrated, and data related to its geographical distribution, its habitat and its phenology are given. From all observations the taxon is the product of a natural crossing between two species belonging to different morphological groups: C. blackii, characterized by a lip more open and fimbriate, and C. purum, which has a globular lip. As a natural hybrid the nothospecies presents a set of intermediate characters when compared to its probable parents, a point discussed in this article. We propose also an identification key to the Catasetum species occurring in Bahia. Besides, because the type material of C. purum could not be located, we propose as a lectotype the illustration published in the original description of the species.